Anticancer potential of phytochemicals against breast cancer: Molecular docking and simulation approach - Ahmed, Bilal; Ashfaq, Usman Ali; Qamar, Muhammad Tahir ul; Ahmad, Matloob (Bangladesh Journal of Pharmacology, 2014)
Breast cancer malignancy is prevailing among the women not only from the developing countries but also from the developed one at the rate of 18% of total population worldwide. One of the main causes of breast cancer is estrogen receptor alpha. Overexpression of estrogen receptor is seen in number of cases of breast cancer. Tamoxifen was used as a reference drug in present study. Almost 80,000 species of plants are used as a source of medicines. Current study was totally based on the screening of phytochemicals to find out the biomolecules having strong bonding actions as compared to tamoxifen. Present study exhibited that 10 molecules (kushenol K, silybin, taxifolin 3-O-acetate, rosemarinic acid, secundifloran, kushenol N, kurarinol, podophyllotoxone, AC1LCW2L, leachianone G) have successful and potential binding with the target molecule as compared to tamoxifen. These molecules can be used for the treatment of breast cancer and birth control.